(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
The existence of various ethnic groups in Sabah has not contributed to miscommunication even though there are a lot differences in terms of religion, customs, language and beliefs. The unique way of life as well as the beliefs of the ethnic Kadazandusun prove the strong influence of their ancestral beliefs persists even in the younger generation. This article is aimed at uncovering the beliefs that underlie the cusotmary practuces of the Kadazandusun as reflected in the short story anthology Tangon. The short stories are analysed using the approach of literary anthropology as a means to examine the preservation of the ethnic identity of the Kadazandusun in Sabah through their beliefs and the continued importance of the Bobolian in their society. The findings show that Sabahan writers successfully incorporate and maintain elements of their traditional beliefs to mark their identity as Kadazandusun of Sabah even till this very day. Keywords: Tangon, Sabah, literary anthropology, beliefs, Kadazandusun, Bobolian, supernatural beings